PICTOGRAM-BASED INFORMATION LEAFLET IN PATIENTS WITH PSORIASIS - Satheendran, Swapna; Nagappa, Anantha Naik; Pai, Sathish (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to evaluate the impact of an information leaflet on the knowledge of disease in patients with psoriasis. Methods: A total of 50 patients with psoriasis on different treatment regimens were selected in the study. The pre- and post-test design (quasi-experimental design) was conducted for user testing of information leaflets (Baker Able design) which covered risk factors, signs and symptoms, and treatment options. The knowledge of psoriasis was assessed before and after the administration of the information leaflet and was compared using paired t-test. Results: At the follow-up interview, it was observed that patients were well informed about their skin disease but had less awareness about the risk factors and methods to cope with the disease. The overall user-testing knowledge assessment mean scores were observed to have significantly improved with p<0.001 after the introduction of the leaflet. Conclusion: The overall user opinion regarding the content of the leaflets was good. This study shows that an information leaflet given to patients with psoriasis can significantly improve their knowledge of the disease.